Nonlinear elastic-plastic stress investigations on two interacting 3-D cracks in offshore pipelines subjected to different loadings - Zhang, Yanmei (2019)
Multiple cracks can be observed in many of engineering structures such as pressure vessels and pipelines. Under continuous loading conditions, these small and closely distanced multiple cracks can grow together into a large one. Subsequently, it will pose a serious challenge to the integrity and safety of the engineering structures. Although a lot of research works were carried out for predicting fatigue growth of multiple cracks, few literatures focusing on nonlinear elastic-plastic analysis of multiple cracks’ fracture behaviors can be referred to. Therefore, to understand the influence of multiple cracks on integrity and safety of offshore pipelines is indeed desirable in engineering practice. In this study the systematic analyses on the fracture behaviors of two collinear 3-D cracks are performed for the pipelines subjected to a series of the loading conditions. A parametric study on the effect of different separation distances of the two interacting collinear cracks is performed. Based on the numerical results, the interaction factor is introduced to quantify the interaction of the two interacting cracks, and the proposed function for interaction factor can be useful for the preliminary fracture assessment of the surface crack affected by the interactions. Moreover, for biaxial loadings, the results indicate that the most severe fracture response can be produced by the tension load combined with high internal pressure.